Kolaborasi Aktor Pada Penanganan Kekerasan terhadap Perempuan Di Kabupaten Aceh Tamiang - Sari, Jayanti; Sriwahyuni, Neni; Susniwati (Asketik: Jurnal Agama dan Perubahan Sosial, 2021)
Women are still afraid to voice the violence that happened to them and choose to remain silent. Violence against women also occurred in Aceh Tamiang District with various forms of violence experienced by them. The purpose of this study is to analyze violence against women in Aceh Tamiang District. The research method used is qualitative with purposive selection of informants and data collection techniques through observation, interviews, and documentation. The results of the study found that the communication built by the Village Community Empowerment Service, Women's Empowerment and Family Planning was still lacking. Added value is public value, which is the result of efficiency, democracy in institutions, and collaboration processes. There is a deliberation process which is a collaboration that forms mutual learning, building communities and employing interactive. In addition, it was found the importance of academic involvement in providing opportunities for women victims of violence to continue their education to a higher level.